The Factors Can Be Affecting To Carbon Emission Disclosure (Study On Energy Sector Companies Listed On The Indonesia Stock Exchange In 2019-2021) - Yuliandhari, Willy Sri; Ayustyara, Dinda (UNIVERSITAS PAKUAN, 2023)
Carbon Emission Disclosure is one part of environmental disclosure is means of information and a form of corporate responsibility for the environment where corporate activities. With the increasing intensity of carbon emissions in Indonesia and pressure from the public, environmental disclosure also includes carbon emission disclosure resulting from company activities, but this report is still voluntary. So that many companies do not report on carbon emission disclosure. This purpose of this research is to determine the impact of profitability, company size, environmental performance and institutional ownership on carbon emission disclosure in energy sector companies listed on the Indonesia Stock Exchange in 2019-2021. The methodology that was employed is quantitative, and the research sample was acquired over a three-year period utilizing a purposive sampling strategy and 11 firms. The analysis used is descriptive statistical analysis and panel data regression analysis using the Eviews 12 application. The study results show profitability, company size, environmental performance and institutional ownership simultaneously affect carbon emission disclosure. Partially, profitability, environmental performance and institutional ownership have no effect on carbon emission disclosure, while company size has a positive effect on carbon emission disclosure